Balancing Herbal Medicine and Functional Food for Prevention and Treatment of Cardiometabolic Diseases through Modulating Gut Microbiota - Lyu, Ming; Wang, Yue-fei; Fan, Guan-wei; Wang, Xiao-ying; Xu, Shuang-yong; Zhu, Yan (Frontiers in Microbiology, 2017)
It has become apparent that gut microbiota is closely associated with cardiometabolic diseases (CMDs), and alteration in microbiome compositions is also linked to the host environment. Next generation sequencing (NGS) has facilitated in-depth studies on the effects of herbal medicine and functional food on gut microbiota. Both herbal medicine and functional food contain fiber, polyphenols and polysaccharides exert prebiotic-like activities in the prevention and treatment of CMDs. The administration of herbal medicine and functional food lead to increased abundance of phylum Bacteroidetes, and genus Akkermansia, Bifidobacteria, Lactobacillus, Bacteroides and Prevotella in the gut, while reducing phylum Firmicutes and Firmicutes/Bacteroidetes ratio. Both herbals and foods interact with gut microbiome point to the microbial metabolites of short-chain fatty acids (SCFAs), bile acids (BAs) and lipopolysaccharides (LPS), which are the preferred mechanisms correlated with metabolic diseases such as type 2 diabetes (T2D), obesity and non-alcoholic fatty liver disease (NAFLD). In addition, trimethylamine (TMA)-N-oxide (TMAO) is recently linked to atherosclerosis (AS) and cardiovascular disease (CVD) risks. Moreover, gut-organ axes may serve as the potential strategy for treating CMDs with the intervention of herbal medicine and functional food. In summary, the overlap between herbal medicine and functional food rich in fiber, polyphenols and polysaccharides play a vital role in modulating gut microbiota (phylum Bacteroidetes, Firmicutes and Firmicutes/Bacteroidetes ratio, and genus Akkermansia, Bifidobacteria, Lactobacillus, Bacteroides and Prevotella) through SCFAs, BAs, LPS and TMAO signaling regarding CMDs. Targeting gut-organs axas may serve as a new therapeutic strategy for CMDs by herbal medicine and functional food in the future. This review aims to summarize the overlap between herbal medicine and functional food used for the prevention and treatment of CMDs through modulation of gut microbiota.